2022
DOI: 10.1021/acsomega.2c05307
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of DprE1 Inhibitors against Mycobacterium tuberculosis: Computational Analysis of Physicochemical and ADMET Properties

Abstract: Decaprenylphosphoryl-β-d-ribose 2′-epimerase (DprE1) is a critical flavoenzyme in Mycobacterium tuberculosis, catalyzing a vital step in the production of lipoarabinomannan and arabinogalactan, both of which are essential for cell wall biosynthesis. Due to its periplasmic localization, DprE1 is a susceptible target, and several compounds with diverse scaffolds have been discovered that inhibit this enzyme, covalently or noncovalently. We evaluated a total of ∼1519 DprE1 inhibitors disclosed in the literature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 153 publications
2
14
0
Order By: Relevance
“…Amado et al [13b] . performed a comprehensive analysis of physicochemical descriptors and ADMET properties for 1,519 DprE1 inhibitors reported in the literature between 2009 and April 2022.…”
Section: The Emergence Of Covalent Dpre1 Inhibitorsmentioning
confidence: 99%
“…Amado et al [13b] . performed a comprehensive analysis of physicochemical descriptors and ADMET properties for 1,519 DprE1 inhibitors reported in the literature between 2009 and April 2022.…”
Section: The Emergence Of Covalent Dpre1 Inhibitorsmentioning
confidence: 99%
“…In contrast, OPC‐167832 is a carbostyril derivative and TBA‐7371 is a 1,4‐azaindole, both of which are noncovalent DprE1 inhibitors. Recent research have identified a variety of new DprE1 inhibitors, including benzothiazinones containing 2‐benzyl‐2,7‐diazaspiro[3.5]nonane, 116 benzothiopyranones, 117 morpholino‐pyrimidines, 118 hydantoins, 119 thiophene‐arylamides, 120 4‐aminoquinolone piperidine amides, 121 2‐carboxyquinoxalines, 122 N ‐alkyl‐5‐hydroxypyrimidinone carboxamides, 123 selamectin, 124 with promising antimycobacterial activity 125 …”
Section: Drug Targets and Inhibitors Targeting Mtbmentioning
confidence: 99%
“…Thus far, more than 600 examples of 8-nitro-BTZs have been reported, of which nearly 90% exhibit in vitro activity against M. tuberculosis (MIC < 10 μM). 107 Despite these extensive studies, the effect of side chain at C-2 on the in vitro activity against mycobacteria still lacks a comprehensive understanding. Remarkably, one of two BTZs that have progressed to clinical studies, viz.…”
Section: In Vitro Antimycobacterial Activity and Sarsmentioning
confidence: 99%
“…125 An up-to-date in-depth computational analysis and evaluation of physicochemical descriptors and absorption, distribution, metabolism, excretion and toxicity (ADMET) properties of a total of 41.500 published DprE1 inhibitors against M. tuberculosis including BTZs can be found in the literature. 107…”
Section: Physicochemical and Pharmacokinetic Propertiesmentioning
confidence: 99%